O olhar da bioética no jornalismo científico em mato grosso do sul: Estudo de caso do Telejornal MS Rural - de Almeida, Willem Fernandes [UNESP]; Toniazzo, Gladis Salete Linhares (My University, 2010)
Bioethic is an evidence discipline on the international scientific scene that, with the expansion of its study lines, approach questions about the consequences of scientific development to the environment, the humanity and the planet's life future. This paper explain about the relation of bioethical principles in the practice of scientific journalism, through the analysis of twelve editions of MS Rural, a TV program shown on TV Morena, affiliated broadcast of Rede Globo in Mato Grosso do Sul. By means of the bibliography survey on ethics, bioethics and media, this research argue in a descriptive way, the conscience, the applicability and the implications of the incidence of bioethical principles associated with bioscience, sanity, ecosystems and the society on the journalism practice.
The approach of bioethics in scientific journalism in mato grosso do sul: A case study of rural Telejornal MS Rural
Keywords: Bioethic; Journalism; Media; Television